Fraud auditing and forensic accounting - Singleton, Tommie (Wiley, 2010)
"Completely revised and updated, Fraud Auditing and Forensic Accounting, Fourth Edition reveals how to develop an investigative eye toward both internal and external fraud and provides crucial information on how to deal with it when discovered. With new chapters on the physiological aspects of the fraudster and on fraud response, as well as new material on non-financial aspects of fraud investigation, body language, discourse analysis, and interviewing techniques, this authoritative, timely book equips auditors, investigators, corporate attorneys, and accountants to identify the signs of financial fraud and successfully investigate it"-- c Provided by publisher